A Primeira Guerra do Paraguai : a expedição do império do Brasil a Assunção [1854-5] - Teixeira, Fabiano Barcellos (2012)
We analyze the diplomatic mission sent by the empire of Brazil to Asuncion between 1854-55 and its possible relations with largest South American conflict, the war of Paraguay , occurred between 1864-70. On December 10, 1854, the empire of Brazil shipped to capital of Paraguay over 30 warships, two or three thousand soldiers to perform this operation. The expedition was aimed at ensuring the navigability of the Paraguay River, an important means of communication in Rio de Janeiro with the province of Mato Grosso, and define the boundaries between the two nations.For its part, the Paraguay mobilized about six thousand men to their defence and built fortresses on the banks of the River Paraguay Humaitá for the repulse then imminent imperial aggression. Pedro Ferreira de Oliveira, chief of the imperial fleet, was appointed to command of expedition. The squad did not go into combat. On April 27, 1855, Pedro Ferreira de Oliveira signed treaty of friendship, commerce and navigation with the government of Paraguay. However, the agreement was rejected by the imperial parliament, for the free navigation of the Paraguay River was not obtained. The mission did not achieve its main objectives, but may have ensured the relative success of Allied troops in battles that occurred in the decade after the aforementioned operation. Despite winning, at least tactically, the Paraguayan government failed to adjust lasting diplomatic agreement with the Empire, and in the decade following the Great War broke out in South America. The expedition to may have important meaning to the context that led to the "war of Paraguay", or the Triple Alliance of 1864-70. Despite its importance, this expedition was not such a distinction by historiography and is yet to be better understood